Penerapan Protokol Kesehatan dan Dampak Covid-19 Terhadap Harga Komoditas Perikanan dan Aktivitas Penangkapan - Dwi Mardhia; Neri Kautsari; Lalu Ilham Syaputra; Wahyu Ramdhani; Chandra Okta Rasiardhi (Indonesian Journal of Applied Science and Technology, 2020)
The COVID-19 pandemic is a problem faced by almost all countries in the world including Indonesia which has implications for the fisheries sector. Fisheries sector players including vulnerable groups affected by COVID-19. This study aim is to analyze the application of health regulation that contain understanding and application of health regulations on fisheries and the impact of COVID-19 on commodity prices and fishing activities. The method used in this study is an online survey through a questionnaire using Google forms and in-depth interviews through the telephone network involving 45 respondents of fishermen. The survey results show that 93% of fishermen knew enough about the COVID-19 pandemic, 84% were quite worried, 7% were very worried and 9% had no effect. Most fishermen have implemented health protocol efforts including activities to wear masks, avoid shaking hands and washing hands with soap. Pandemic has an impact on the decline in fishery commodity prices by 10%. The impact of the pandemic on fishing activities is the delays in the delivery of commodity products, the decrease in the number of fishing, the decrease in the number of catches and demand for catches and the decrease in fishermen's income.